The Rig-Vedic and post-Rig-Vedic polity: (1500 BCE - 500 BCE) - Prasad, R. U. S. (Vernon Press, 2015)
The book critically examines and assesses the literary evidence available through Vedic and allied literature portraying the nature of Vedic polity, the functionalities of its various institutions, and the various social and religious practices. The book is not a narrative but critically examines the nature of changes in a host of these areas that occurred at each stage of Vedic polity from early Vedic period to post Rig-Vedic period.--